Agir bibliotecário nas bibliotecas universitárias públicas estaduais brasileiras, em contexto da ciência aberta - Silva, Fernanda Mirelle de Almeida (2023)
Open science is a transparent, accessible and free scientific practice that allows and encourages joint collaboration between researchers, research groups, professionals and society, managing and sharing data, methods, resources and tools to streamline the creation of knowledge and accelerate scientific advances on a global scale. Faced with the need to consider professional performance in the face of the differentiated and provocative scenario, the main objective of the thesis focuses on analyzing the librarian's action in the actions developed by brazilian state public universities that are dynamized by open science. The specific objectives correspond to: a) to know the actions and services of the state public university libraries directed to the university community, from the institutional sites; b) to identify how librarian informational support occurs in the scientific demands of the brazilian state public university; c) to investigate tools, resources and scientific-informational practices from open science that involve the university library; d) to investigate the skills necessary for librarianship in environments promoted by Open Science. The methodological outline of the thesis takes place through the poles of the quadripolar method, which provide greater perception of flows, dialogues and practices, in a synchronic engagement of the research, as well as distinguishing particularities that each moment of the study has, in a deep visualization of the stages. The theoretical framework is constructed, contextualizing the most significant theoretical and practical approaches of open science with the actions of libraries and librarians, identifying competences to act, in a perspective of proactive and critical analysis, to meet the professional demands arising from the contexts of science open. The study collaborates, professionally and scientifically, by contributing to a dialogued, proactive and responsible librarianship in the brazilian scientific development and in the promotion of open science. The results expose the virtual institutional profile of 39 state public university libraries, highlighting information, organizational structure, collections, services, communication channels and informational and administrative contents. From the application of criteria, the research subjects present themselves through the institutional profile of performance reporting services, engagement with the university experience, institutional support, continuing education, improvement of librarians, informational actions in university environments influenced by open science. Finally, some considerations are highlighted: there are actions and adoptions arising from scientific openness, consciously and/or unconsciously; librarian action is perceived as embryonic and sometimes involuntary; acting as a librarian in open science requires skill, opportunity and managerial/institutional decision; the understanding of BUPE's librarian action projects the need to be seen, by oneself, by peers, by users and by the institution.